1995
DOI: 10.1088/0953-8984/7/50/010
|View full text |Cite
|
Sign up to set email alerts
|

Elastic/anelastic behaviour during the phase transition in spinel LiMn2O4

Abstract: Both the Young`s modulus sound velocity (VE) and the internal friction (Q-1) have been measured for a polycrystalline sample of LiMn2O4 in the temperature range between 35 and 350 K, using a vibrating-reed technique. The resonance frequency (fr) employed for the measurement ranged from 0.81 kHz to 2.69 kHz at 300 K. At fr(300 K)=0.81 kHz, as temperature is lowered from 350 K, VE decreases down to 225 K (TA) Then, VE increases rapidly but monotonically with lowering temperature, though the magnitude of the slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 20 publications
3
37
2
Order By: Relevance
“…5b) follows analogous conductivity features in the same temperature range (Fig. 5a), corresponding to the presence of a structural transition already observed (10,26). This transition was attributed to the Jahn-Teller effect on the octahedral coordination of the Mn> ions.…”
Section: Discussionsupporting
confidence: 73%
“…5b) follows analogous conductivity features in the same temperature range (Fig. 5a), corresponding to the presence of a structural transition already observed (10,26). This transition was attributed to the Jahn-Teller effect on the octahedral coordination of the Mn> ions.…”
Section: Discussionsupporting
confidence: 73%
“…The nano-indentation experiments on the LiMn 2 O 4 thin-film surface before the cycling tests, repeated 100 times at random locations with the same interval, indicated that the average elastic modulus of the pristine LiMn 2 O 4 was 13.5 GPa, with a standard deviation of 3.1 GPa. This is comparable to the elastic modulus of LiMn 2 O 4 reported by Sugiyama et al 24 The SEI thickness, measured by the nano-indentation technique using an AFM, showed a broad distribution and its range increased with an increasing number of cycles. The histogram of SEI thickness as a function of cycle number, shown in Fig.…”
supporting
confidence: 88%
“…Some controversy exists in the literature [2,[7][8][9] on the magnetic susceptibility of the stoichiometric LiMn 2 0 4 which shows a sample dependent behaviour, particularly at low temperature. The spread of results may arise from differences in the preparation methods, which can easily introduce unwanted spurious phases [10].…”
Section: +mentioning
confidence: 99%